After Impressionism inventing modern art - Stevens, MaryAnne 1947-; Alambritis, Maria; Domercq, Julien; De Mille, Charlotte; Milner, John 1946-; Ralston, Daniel Sobrino; Riopelle, Christopher 1950-; Smith, Camilla; Wieber, Sabine (National Gallery Global, 2023)
Through the 1880s the very essence of representation, meaning and process in Western art were profoundly interrogated. Plausible representations of the external world were cast aside in favour of non-naturalism expressed in varying degrees, from modest distortions of reality to pure abstraction. The decades that followed, up to the outbreak of the First World War in 1914, were a complex, vibrant period of artistic questioning, searching, risk-taking and innovation. Concentrating on this period of great upheaval, this book will explore the constructive dialogue between painting and sculpture, and the influential roles played by three giants of the era, Paul Cézanne, Paul Gauguin and Vincent van Gogh, across European art as a whole. While acknowledging the centrality of Paris as a cultural capital, it will also uniquely highlight other centres of artistic ferment in Europe, from Brussels and Barcelona to Berlin and Vienna, and track the variety of routes into modernism in the early twentieth century. This fully illustrated catalogue will contain four essays, introductions to each city of ferment and biographies of the artists. Exhibition: The National Gallery, London, UK (25.03. - 13.08.2023)
Rückseite Titelblatt: Published to accompany the exhibition "After Impressionism: Inventing Modern Art", The National Gallery, London, 25 March - 13 August 2023
Keywords: Nachimpressionismus; Moderne; Art, Modern / 19th century / Exhibitions; Art, Modern / 20th century / Exhibitions; Art / 19e siècle / Expositions; Art / 20e siècle / Expositions; ART / European; Art, Modern; 1800-1999; Exhibition catalogs; Ausstellungskatalog -- The National Gallery -- 25.03.2023-13.08.2023 -- London